2020
DOI: 10.1186/s12886-020-01746-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of atropine to control myopia progression: a systematic review and meta-analysis

Abstract: Background The effect and safety of atropine on delaying the progression of myopia has been extensively studied, but its optimal dose is still unclear. Therefore, the purpose of this meta-analysis is to systematically evaluate the safety and effectiveness of atropine in controlling the progression of myopia, and to explore the relationship between the dose of atropine and the effectiveness of controlling the progression of myopia. Methods This work was done through the data searched from PubMed, MEDLINE, EMBA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
2
16
0
4
Order By: Relevance
“…However, there are still some uncertainties and controversies. Some studies reported that the efficacy of atropine was dose-related ( 17 ), whereas others found that efficacy of atropine was dose-independent within the range of 0.01–1% ( 13 , 18 ). Most RCTs and cohort studies reported a first-year protective effect on myopia, whereas the Atropine for the Treatment of Myopia 2 (ATOM 2) study showed a better effect of 0.01% atropine treatment in the second year than in the first year, and it is recommended that the initial treatment of 0.01% atropine should last at least 2 years ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still some uncertainties and controversies. Some studies reported that the efficacy of atropine was dose-related ( 17 ), whereas others found that efficacy of atropine was dose-independent within the range of 0.01–1% ( 13 , 18 ). Most RCTs and cohort studies reported a first-year protective effect on myopia, whereas the Atropine for the Treatment of Myopia 2 (ATOM 2) study showed a better effect of 0.01% atropine treatment in the second year than in the first year, and it is recommended that the initial treatment of 0.01% atropine should last at least 2 years ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous systematic review and meta-analysis have identified the efficacy and safety of atropine with ambiguous findings [ 20 23 ]. It was shown that the optimal dose of atropine may be 0.5% and 1% by Song et al [ 21 ] and equally beneficial by Gong et al [ 20 ], 0.01% by Zhao et al [ 22 ], and 0.05% by Zhao et al [ 23 ], but lacking consensus on atropine dose. As new clinical trials continually emerge, it is essential to conduct a meta-analysis to identify the optimal dose of atropine.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of atropine (a non-selective antagonist of muscarinic acetylcholine receptors) to prevent myopia progression in children has been studied widely. Different concentrations of atropine (0.01% to 1%) have been shown to inhibit myopic progression effectively [14][15][16]. However, high dose atropine has been subject to significant adverse effects such as blurred near vision, photophobia and rebound phenomenon after treatment cessation [16].…”
Section: Introductionmentioning
confidence: 99%